Answers

2016-04-22T11:25:00+05:30
Let x2 -1 =0  ( it is factor)                                                                                                  X= 1 and X = -1 ( by using the formula a2 - b2)                                                          consider the equation as P(x) = Px3 + 2x2 - 3x +q                                                      now put the value of x =1 in p (x)                                                                                    you will get the value of p and q.
0